Development of Bureaucracy in Administrative Management (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the history of the origin of bureaucratism, the rational management system, the failure of public administration, red tape, heavy procedures, administrative obstacles, the peculiarity of the rational bureaucracy system. Also, scientific researches and conclusions of foreign and our country's scientists on the role of administrative bureaucracy in resolving disputes arising in state administration were analyzed and studied.